AMIGO2 characterizes cancer-associated fibroblasts in metastatic colon cancer and induces the release of paracrine active tumorigenic secretomes - Yong, Yong-song; Demmler, Richard; Zohud, Bisan; Fang, Qi; Zhang, Tong; Zhou, Yonghua; Petter, Katja; Flierl, Christian; Gass, Tobias; Geppert, Carol-Immanuel; Merkel, Susanne; Schellerer, Vera; et al. (Journal of Pathology, 2024)
Secretomes of cancer-associated fibroblasts (CAFs) in colorectal cancer (CRC) contribute to malignancy. Detailed knowledge is available on the components and functions of CAF secretomes. Little is known about the regulation of CAF secretomes. Here, we searched for receptor-like membrane-bound molecules in CAFs, which may regulate the production and release of tumor-activating secretomes. The adhesion molecule with Ig-like domain 2 (AMIGO2) was significantly upregulated in cultivated CAFs compared to normal tissue-associated fibroblasts (NAFs), and this was confirmed in patient-derived tissues. AMIGO2 expression was low or absent in healthy colon, significantly increased in fibroblasts of primary CRC, and highest in the stromal tissues of CRC-derived liver metastases. AMIGO2 expression in CAFs correlated with a higher T-category, increased lymph node metastasis, progressed tumor stages and was associated with reduced survival in different cohorts of CRC patients. Interestingly, AMIGO2 expression was induced by transforming growth factor-β and higher in female patients, who exhibit a more aggressive disease course. In functional studies, conditioned media of NAFs with experimentally induced AMIGO2 overexpression enhanced proliferation and migration of different CRC tumor cells, while siRNA-mediated inhibition of AMIGO2 in CAFs attenuated these effects. Accordingly, therapeutic inhibition of the receptor-like AMIGO2 protein in CRC CAFs could prevent tumorigenic secretomes in CRC. © 2024 The Author(s). The Journal of Pathology published by John Wiley & Sons Ltd on behalf of The Pathological Society of Great Britain and Ireland.
CRIS-Team Scopus Importer:2024-11-22
Keywords: cancer-associated fibroblasts; colorectal cancer; secretion; secretomes; tumor microenvironment

Neutrophil extracellular traps drive epithelial‐mesenchymal transition of human colon cancer - Stehr, Antonia; Wang, Guangxia; Demmler, Richard; Stemmler, Marc; Straube, Julia; Tripal, Philipp; Schmid, Benjamin; Geppert, Carol-Immanuel; Hartmann, Arndt; Munoz, Luis Enrique; Schoen, Janina; Völkl, Simon; et al. (Journal of Pathology, 2021)
Neutrophil extracellular traps (NETs) are extracellular structures, composed of nuclear DNA and various proteins released from neutrophils. Evidence is growing that NETs exert manifold functions in infection, immunity, and cancer. Recently, NETs have been detected in colorectal cancer (CRC) tissues but their association with disease progression and putative functional impact on tumourigenesis remained elusive. Using high-resolution stimulated emission depletion (STED) microscopy we showed that citrullinated histone H3 (H3cit) is sufficient to specifically detect citrullinated NETs in colon cancer tissues. Among other evidence this was supported by the close association of H3cit with de-condensed extracellular DNA, the hallmark of NETs. Extracellular DNA was reliably differentiated from nuclear condensed DNA by staining with an anti-DNA-antibody providing a novel and valuable tool to detect NETs in FFPE tissues. Using these markers, the clinical association of NETs has been investigated in a cohort of 85 patients with colon cancer. NETs were frequently detected (n = 37/n = 85, 44%) in colon cancer tissue sections and preferentially localized either only in the tumour centre or both, in the tumour centre and the invasive front. Of note, citrullinated NETs were significantly associated with high histopathologic tumour grades and lymph node metastasis. In vitro, purified NETs induced filopodia formation and cell motility in CRC cell lines. This was associated with increased expression of mesenchymal marker mRNAs (vimentin [VIM], fibronectin [FN1]) and epithelial- mesenchymal transition (EMT) promoting transcription factors (ZEB1 and Slug [SNAI2]) as well as decreased expression of the epithelial markers E-cadherin (CDH1) and EpCAM (EPCAM). These findings indicated that NETs activate an EMT-like process in CRC cells and may contribute to the metastatic progression of CRC.
Keywords: epithelial–mesenchymal transition (EMT); colorectal neoplasms; stimulated emission depletion (STED) microscopy; neutrophils; migration; extracellular traps

Pathological function of neutrophil extracellular traps in human colon cancer - Stehr, Antonia; Wang, Guangxia; Demmler, Richard; Stemmler, Marc; Tripal, Philipp; Geppert, Carol-Immanuel; Merkel, Susanne; Herrmann, Martin; Stürzl, Michael (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16

Rapid qPCR-based quantitative immune cell phenotyping in mouse tissues - Huang, Jinghao; Demmler, Richard; Mohamed Abdou, Mariam; Thoma, Oana-Maria; Weigmann, Benno; Waldner, Maximilian; Stürzl, Michael; Naschberger, Elisabeth (Journal of Investigative Medicine, 2024)
The immune microenvironment plays an important role in the regulation of diseases. The characterization of the cellular composition of immune cell infiltrates in diseases and respective models is a major task in pathogenesis research and diagnostics. For the assessment of immune cell populations in tissues, fluorescence-activated cell sorting (FACS) or immunohistochemistry (IHC) are the two most common techniques presently applied, but they are cost intensive, laborious, and sometimes limited by the availability of suitable antibodies. Complementary rapid qPCR-based approaches exist for the human situation but are lacking for experimental mouse models. Accordingly, we developed a robust, rapid RT-qPCR-based approach to determine and quantify the abundance of prominent immune cell populations such as T cells, helper T (Th) cells, cytotoxic T cells, Th1 cells, B cells, and macrophages in mouse tissues. The results were independently validated by the gold standards IHC and FACS in corresponding tissues and showed high concordance.
CRIS-Team Scopus Importer:2023-12-22
Keywords: FACS; IHC; immune cell phenotyping; mouse tissue; RT-qPCR

Tumor microenvironment-dependent epigenetic imprinting in the vasculature predicts colon cancer outcome - Naschberger, Elisabeth; Fuchs, Maximilian; Dickel, Nicholas; Kunz, Meik; Popp, Bernt; Anchang, Charles Gwellem; Demmler, Richard; Lyu, Yanmin; Uebe, Steffen; Ekici, Arif Bülent; Geppert, Carol-Immanuel; Hartmann, Arndt; et al. (Cancer Communications, 2023)
CRIS-Team Scopus Importer:2023-10-27